Research on horizontal nonlinear sub-harmonic vibration characteristics and stability control of rolling mill roll system - Li Jiang; Ting Yang; Wei Shi; Jiaquan Xie (Scientific Reports)
Abstract In this paper, the main content is analyzing the combined resonance characteristics of the roller system. Firstly, established a horizontal nonlinear vibration model with fractional-order by considering the nonlinear stiffness and nonlinear damping between the roller and the material. Secondly, the multi-scale method is applied to solve the non-resonance, sub-harmonic resonance and super-harmonic resonance of the roller system. The analytical solution and the amplitude-frequency characteristic equations are obtained. Then, The relationship between the influence of different parameters on the sub-harmonic vibration of the roll system is investigated, and the results show that the nonlinear damping coefficient, nonlinear stiffness coefficient, linear stiffness coefficient and excitation force amplitude all affect the sub-harmonic vibration range and co-oscillation amplitude, and the change of the stiffness coefficient induces the system oscillation. Last, a linear and nonlinear optimal feedback controller is designed to control the sub-harmonic resonance and super-harmonic resonance phenomena of the roll system. Where the sub-harmonic resonance control parameters are selected in the range g 2 ∈ (−0.32,0), 3.7 > g 3 > 2.67, and the super-harmonic resonance control parameters are selected in the range g 2 > 0, 0.5 < g 3 < 2.5. The correctness of the theoretical study is verified by field experiments.